RETRACTED: Mechanism of action of Asparagus officinalis extract against multiple myeloma using bioinformatics tools, in silico and in vitro study - Li, Yanju; Yang, Xu; Wang, Feiqing; Zhao, Jianing; Zhang, Chike; Wu, Dan; Yang, Bo; Gao, Rui; Zhao, Peng; Zan, Yun; Su, Min; He, Zhixu; et al. (Frontiers in Pharmacology, 2023)
Asparagus (Asparagus officinalis) is a perennial flowering plant species. Its main components have tumor-prevention, immune system-enhancement, and anti-inflammation effects. However, the interaction of bioactive substances from asparagus with the targets involved in multiple myeloma (MM) has not been elucidated. We explored the mechanism of action of asparagus in MM through network pharmacology and experimental verification. The active ingredients and corresponding targets of asparagus were acquired from the Traditional Chinese Medicine System Pharmacology database, followed by identification of MM-related target genes using GeneCards and Online Mendelian Inheritance in Man databases, which were matched with the potential targets of asparagus. Potential targets were identified and a target network of traditional Chinese medicine was constructed. The STRING database and Cytoscape were utilized to create protein–protein interaction (PPI) networks and further screening of core targets. The intersection of target genes and core target genes of the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathway was enriched, the top-five core target genes were selected, and the binding affinity of corresponding compounds to the top-five core targets was analyzed using molecular docking. Network pharmacology identified nine active components of asparagus from databases based on oral bioavailability and drug similarity, and predicted 157 potential targets related to asparagus. Enrichment analyses showed that “steroid receptor activity” and the “PI3K/AKT signaling pathway” were the most enriched biological process and signaling pathway, respectively. According to the top-10 core genes and targets of the PPI pathway, AKT1, interleukin (IL)-6, vascular endothelial growth factor (VEGF)A, MYC, and epidermal growth factor receptor (EGFR) were selected for molecular docking. The latter showed that five core targets of the PI3K/AKT signaling pathway could bind to quercetin, among which EGFR, IL-6, and MYC showed strong docking, and the diosgenin ligand could bind to VEGFA. Cell experiments showed that asparagus, through the PI3K/AKT/NF-κB pathway, inhibited the proliferation and migration of MM cells, and caused retardation and apoptosis of MM cells in the G0/G1 phase. In this study, the anti-cancer activity of asparagus against MM was demonstrated using network pharmacology, and potential pharmacological mechanisms were inferred using in vitro experimental data.